39. HIV TESTING FREQUENCY AND ASSOCIATED FACTORS AMONG MALE PEOPLE WHO INJIECT DRUGS OF QUANG NINH PROVINCES IN 2021 (Vietnam Journal of Community Medicine, 2025)
HIV testing is the first step of an ongoing link between HIV diagnosis, care, and treatment that contributes to reducing HIV transmission in the community. A cross-sectional study among 300 male people who inject drugs (PWID) aged 16 years and older, living in 5 districts of Quang Ninh province was conducted in 2021 to describe the status of HIV testing in the past 12 months among PWID. Research results show that the percentage of PWID who had ever tested for HIV or tested for HIV in the past year was 98.3% and 52.7%, respectively. Two factors were found to increased HIV testing in the past 12 months including: using only heroin (PR=1.23; 95% KTC: 1.01-1.51; p=0.039); having received free condoms in the past 6 months (PR=1.58; 95% CI: 1.31-1.91; p=0.001). Otherwise, two factors were found that reduced HIV testing in the last year among PWID: had ever shared needles (PR=0.63; 95% KTC: 0.46-0.85; p=0.003) and had ever sex with female sex worker (PR=0.69; 95% KTC: 0.52-0.92; p=0.011). It is necessary to diversify of HIV testing approaches to improve the utilization of HIV testing among PWID.
Keywords: HIV testing; people who inject drugs (PWID); Quang Ninh; 2021